Business External Commercial Dynamics of Argentina in the Government of Cambiemos (2015-2019) - García Zanotti, Gustavo; Schorr, Martín (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper aims to analyze the foreign trade flows of the largest companies in Argentina during the government of Cambiemos alliance (2015-2019). The institutional transformations during this period had a clear orthodox approach and, among other things, led to a deindustrialization and reprimarization process of the specialization profile and international insertion. On the other hand, due to the importance that the largest companies have in the economy, their behavior explained the course on the external sector in this neoliberal experience. This economic power showed great dynamism in trade flows, either thanks to the increase in exports, mostly associated with the exploitation of natural resources, or to its role in the import boom of goods that competed with national production. Finally, we highlight that the management of Cambiemos made relevant changes in the rules of the game of foreign trade. In accordance with the prevailing orthodox approach, in the studied stage various policies were applied that, in their articulation, led to a sharp process of deindustrialization and reprimarization of the profile of specialization and insertion of Argentina in the world market.